Cost-effectiveness of preemptive skin treatment to prevent skin-toxicity caused by panitumumab in third-line therapy for KRAS wild type metastatic colorectal cancer in Japan - Munenobu Kashiwa; Ryo Matsushita (BMC, 2021)
Abstract Background Clinical management of skin-toxicity associated with the use of anti-Epidermal Growth Factor Receptor (EGFR) antibodies to treat colorectal cancer maintains quality of life of patients with colorectal cancer. Results of clinical trials have recommended the efficacy of prophylactic treatment, but the cost-effectiveness is unclear. This study examined the cost-effectiveness of preventive skin care for skin-toxicity caused by panitumumab in third-line therapy for KRAS wild type metastatic colorectal cancer from the perspective of the Japanese healthcare payer. Methods The data source was J-STEPP trial, which compared preemptive skin treatment with reactive treatment in third-line panitumumab therapy for KRAS wild type metastatic colorectal cancer in Japan. The costs and effectiveness of preemptive treatment was compared with reactive treatment in a 3-year time horizon using a 4-state partitioned survival analysis. The health outcome was quality-adjusted life-years (QALYs). The costs were 2020 revisions to the drug prices. The robustness of the model was verified by one-way sensitivity analysis and a probabilistic sensitivity analysis (PSA). A 2% annual discount was applied to the expenses and QALYs. Willingness-to-pay (WTP) threshold of 5 million JPY was used. Results Preemptive treatment had incremental effects of 0.0029 QALYs, incremental costs of 5300 JPY (48.6 USD), and incremental cost-effectiveness ratios (ICER) of 1,843,395 JPY (16,912 USD) per QALY. The variability of preemptive and reactive treatment costs for skin-toxicity and the disutility of skin-toxicity had a large impact on ICER. From PSA, the cost-effectiveness rate of preemptive treatment was 75.0%. Conclusions The cost to effectiveness of preemptive treatment to prevent skin-toxicity caused by panitumumab in third-line therapy for KRAS wild type mCRC is not high.